An Existence Result of Positive Solutions for Fully Second-Order Boundary Value Problems. (16th December 2015) - Li, Yongxiang; Shang, Yaya
Abstract : An existence result of positive solutions is obtained for the fully second-order boundary value problem - u ′′ ( t ) = f ( t, u ( t ), u ′ ( t ) ), t ∈ [ 0, 1 ], u ( 0 ) = u ( 1 ) = 0, wheref : [ 0, 1 ] × R + × R → R is continuous. The nonlinearityf ( t, x, y ) may be sign-changing and superlinear growth onx andy . Our discussion is based on the method of lower and upper solution.